2005
DOI: 10.1088/0953-8984/17/19/l01
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the coexistence of ferroelectric and antiferroelectric states on the lead lanthanum zirconate titanate crystal structure

Abstract: We present results of detailed investigation of the crystal structure of Pb1−3x/2Lax(Zr1−yTiy)O3 solid solutions. In this letter our attention is concentrated on the series of solid solutions with x = 6% usually referred to as relaxor ferroelectrics. We have established the reasons for the non-cubic crystal structure of these solid solutions at the temperatures below TC. It is demonstrated that the peculiarities of the properties of Pb1−3x/2Lax(Zr1−yTiy)O3 depend on the position of a particular solid soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…Such AFE is in-line with the significant sum of the Fourier transforms of Fig. 2b and with the predictions of the importance of the antiferroelectric interactions on relaxor properties [37].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Such AFE is in-line with the significant sum of the Fourier transforms of Fig. 2b and with the predictions of the importance of the antiferroelectric interactions on relaxor properties [37].…”
supporting
confidence: 88%
“…[35] and their size is estimated [36] as s =< N 2 P N R > / < N P N R > , where N P N R is the number of the sites belonging to a particular polar nanoregion while <> denotes averages over the different PNRs. Figure 2a Moreover, various studies suggested that antiferroelectricity (AFE) also plays some role in relaxor ferroelectrics [31,[37][38][39]. To check such fact and determine how such AFE depends on short-range chemical order in PMN, we computed the magnitudes of the Fourier transform [40] of the x-components of the local modes in the considered supercells [41].…”
mentioning
confidence: 99%
“…Transmission electron studies (TEM) revealed a rhombohedral macroscopic symmetry of PLZT x/90/10 for small amount of La (x < 2) and tetragonal together with an incommensurate structure for x > 4 [14]. Ishchuk et al [16] reported difficulties in the structure identification, while Refs. [16e19] refined the composition PLZT 4/ 90/10 as orthorhombic instead of tetragonal.…”
Section: Introductionmentioning
confidence: 99%
“…Such local decomposition of the solid solution in the vicinity of CIPB in the PZT-based solid solutions has been detected and studied in detail. [9][10][11][12] X-ray and neutron diffraction investigations of the crystal structure of PZT solid solutions from the MPB region of compositions represent the larger group of published studies. These studies are based on the analysis of the profiles of lines of the diffraction pattern due to the elastic scattering of incident radiation.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to elicit directly such-like segregates with the AFE state in the PZT solid solutions at present. It has been done for the PZT-based solid solutions with compositions from the ferroelectricantiferroelectric morphotropic region of the \composition-temperature" phase diagram 9,11,12,15,16,20 (where the sizes of segregates were of the order of several tens of nanometer). In addition to that, several recently appeared publications pointed out the possibility of existence of the AFE ordering in the PZT solid solutions with compositions from the MPB region (the region between the tetragonal and rhombohedral phases) of the phase diagram.…”
Section: Introductionmentioning
confidence: 99%